Changes in structural and chemical composition of insoluble dietary fibers bound phenolic complexes from grape pomace by alkaline hydrolysis treatment - JIANG,Guihun (2022)
Abstract This study was aimed at explanation of evolution process of bound phenolics from IDF through structural modifications after alkaline hydrolysis along with free phenolics and functional characteristics. SEM results depicted that IDF with bound phenolics exhibited denser, more compact and tubular shape whereas, the surface features of alkali-hydrolyzed residue exhibited clear fragmentation, wrinkling and porosity on outside surfaces. Microstructure changes due to alkaline hydrolysis caused disintegration of linkages among hemicellulose and cellulose microfibers. As evident from the FTIR spectra, both IDF samples (with phenolic) and alkali-soluble residue (IDF without phenolics) exhibited resemblance in FTIR spectral features and characteristics bonds. Overall, the peak positions of IDF samples and alkali-hydrolyzed residue did not show any significant change, which was indicative of the fact that no major alterations were occurred in crystalline structures of IDF due to alkali-hydrolysis treatment. IDF-bound phenolic complexes showed the highest TPC, ABTS and FRAP than SDF. In IDF alkaline extracts, total 6 phenolic compounds were detected through HPLC. The identified phenolic compounds were as; salicylic acid, chlorogenic acid, syringic acid, epigallocatechin, p-coumaric acid and ferulic acid. These results demonstrated that higher antioxidant activity of dietary fiber would be related to bound phenolics.